THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY AND ORGANIZATIONAL COMMITMENT ON THE DECISION TO USE ISLAMIC BANKS SERVICES CASE STUDY AT MUHAMMADIYAH SCHOOL IN MEDAN CITY - Irfan, Irfan; Yovi, Muhammad; Hani, Syafrida (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this study is to examine and analyze the influence of Islamic financial literacy on and organizational commitment to the decision to use Islamic banking services in Muhammadiyah schools or madrasahs in Medan City. The variable measurement scale used in this study is to use ordinal scales, the sample of this study is as many as 60 Muhammadiyah schools/madrasahs. In the city of Medan with respondents in this study 60 principals of Muhammadiyah Schools/Madrasah in the City of Medan. Islamic financial literacy influences not affect the decision to use Islamic banking services, while organizational commitment does not affect the decision to use Islamic banking.